Exploitation and Distribution of Salt in Antiquity: Between the Eastern Adriatic and Dacia - Imamović, Mersiha (Historical Thought, 2025)
This paper examines the methods and techniques of salt production in antiquity, using examples from several well-known sites in Britain. It then turns to the eastern Adriatic coast and Dacia, where salt was exploited and distributed to the interior of the provinces of Dalmatia, Pannonia, and Moesia. Unlike the eastern Adriatic coast, Dacia has been more thoroughly investigated archaeologically, enabling the author to establish analogies concerning the trading practices of the eastern Adriatic saltworks. The paper further analyses the significance of present-day Tuzla in antiquity and explores the factors that may have motivated salt exploitation in this area. Among other indicators, the toponym Salinae, the general scarcity of salt deposits on the Balkan Peninsula, and the fact that rock salt, abundant in the Tuzla region, was more highly valued than sea salt, all point to the area’s significance.